1989
DOI: 10.1002/j.1537-2197.1989.tb11332.x
|View full text |Cite
|
Sign up to set email alerts
|

Inbreeding Depression in Schiedea Globosa and S. Salicaria (Caryophyllaceae), Subdioecious and Gynodioecious Hawaiian Species

Abstract: Progeny produced by inbreeding were compared to progeny derived from outcrosses for gynodioecious Schiedea salicaria and subdioecious S. globosa to assess fitness consequences of breeding system on parental fecundity (seeds per capsule) and progeny measures of fitness (germination, survival, biomass, and number of flowers). Results from both species indicated that inbreeding depression occurred at all measured stages of the life history. In both species, different females showed different levels of inbreeding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
54
1

Year Published

1989
1989
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 24 publications
7
54
1
Order By: Relevance
“…Schiedea has been used to test some of the factors that promote dioecy, e.g. inbreeding depression (Sakai et al, 1989, sex allocation (Sakai et al, 2008;Weller and Sakai, 2005), wind pollination (Golonka et al, 2005;Weller et al, 1998Weller et al, , 2006Weller et al, , 2007, and environmental conditions Sakai and Weller, 1991). However, the number of shifts to dimorphic breeding systems within Schiedea is unknown, as it depends on phylogenetic resolution among the 12 very closely related species in section Schiedea.…”
Section: Evolution Of Breeding Systemsmentioning
confidence: 99%
“…Schiedea has been used to test some of the factors that promote dioecy, e.g. inbreeding depression (Sakai et al, 1989, sex allocation (Sakai et al, 2008;Weller and Sakai, 2005), wind pollination (Golonka et al, 2005;Weller et al, 1998Weller et al, , 2006Weller et al, , 2007, and environmental conditions Sakai and Weller, 1991). However, the number of shifts to dimorphic breeding systems within Schiedea is unknown, as it depends on phylogenetic resolution among the 12 very closely related species in section Schiedea.…”
Section: Evolution Of Breeding Systemsmentioning
confidence: 99%
“…Bush and Smouse 1991; see also Charlesworth and Charlesworth 1987), and to at least two other gynodioecious or dioecious angiosperms endemic to Hawaii: Schiedea salicaria and S. globosa (Sakai et al 1989; total inbreeding depression in S. salicaria 0.62-0.94 in seed set, germination, survival, and fecundity in the glasshouse; total fitness of unknown mixture of half and full sib matings relative to outcrosses in S. globosa 0.51-1 in the same fitness components). Moreover, the individual components of inbreeding depression in B. sandvicensis are comparable to those of other angiosperms (usually measured in the glasshouse) whose total inbreeding depression is unknown (Agren and Willson 1991;Assouad et al 1978;Manasse and Pinney 1991;Kohn 1988;Jain 1978).…”
Section: Relative Ovule Success Female Frequency and Biparental Inbmentioning
confidence: 99%
“…Although this controversy was never resolved, empirical work has demonstrated that sources of the female advantage clearly vary by species. A large inbreeding depression has been observed in some gynodioecious species (Kohn 1988;Sakai et al 1989), and either a low inbreeding depression or low selfing rate in others (Eckhart 1992;Krohne et al 1980). Maternal effects may cause greater fecundity of females (Eckhart 1992;Shykoff 1988;Delph 1990a), or greater germination rate of their seed (Ashman 1992).…”
mentioning
confidence: 99%
“…Most studies that have measured family-level inbreeding depression have found it to vary among families (e.g., Sakai et al 1989;Å gren and Schemske 1993;Holtsford 1996;. Differences between levels of inbreeding depression as measured for individual families does not in itself constitute evidence for lineage-specific inbreeding depression related to the mating system.…”
mentioning
confidence: 99%